Analisis Pengelolaan Wilayah Konservasi Mangrove Berdasarkan Pendekatan Community Based Conservation di Kabupaten Sidoarjo - Anisatul Septian Ika Candra; Anggraeny Puspaningtyas; Dida Rahmadanik (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2025)
This study aims to analyze the management of mangrove conservation areas in Sidoarjo Regency using the Community Based Conservation (CBC) approach. Mangrove forests play a vital role in maintaining coastal ecosystem balance, yet their existence continues to decline due to land conversion, weak regulations, and low public awareness. The CBC approach emphasizes active community participation in sustainable conservation efforts. This research uses a qualitative method with data collection techniques including interviews, observations, and documentation. The analysis focuses on four CBC indicators: Enabling Conditions, CBC Emergence, CBC Persistence, and CBC Diffusion. The findings indicate that mangrove conservation management in Sidoarjo is not yet optimal due to weak institutional structures, limited public participation, and a lack of cross-sectoral policy integration. It is necessary to establish local regulations, strengthen local institutions such as Community Forestry Groups (KTH), and foster multi-stakeholder collaboration, including the utilization of CSR funding, to support sustainable conservation. This study recommends the formulation of specific local policies and collaborative models for community-based mangrove conservation to promote sustainable coastal development.